2000
DOI: 10.1002/1099-1026(200005/06)15:3<151::aid-ffj884>3.3.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil of Baccharis cordobensis Heering

Abstract: The essential oil of the aerial parts of Baccharis cordobensis was examined by GC and GC–MS. The major constituents were trans‐nerolidol (15.8%), T‐cadinol (14.7%) and cubenol (8.8%). Copyright © 2000 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The remaining structures were identified by comparison with library information on MS and RI data. In general, earlier papers (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) showed that, although the main component may vary, the sesquiterpene fraction is usually the dominant one. Likewise, the sesquiterpene fraction constituted the major part of the oil from B. elaeoides, where as the oil of B. magellanica was mainly constituted of the monoterpenes 4-hydroxyacetophenone and massioa lactone.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The remaining structures were identified by comparison with library information on MS and RI data. In general, earlier papers (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) showed that, although the main component may vary, the sesquiterpene fraction is usually the dominant one. Likewise, the sesquiterpene fraction constituted the major part of the oil from B. elaeoides, where as the oil of B. magellanica was mainly constituted of the monoterpenes 4-hydroxyacetophenone and massioa lactone.…”
Section: Resultsmentioning
confidence: 99%
“…Several of the terpenoids identified in this study have previously been reported from other Baccharis species. As they are widely distributed over the subsections, no taxonomic relationship can be established at the generic level (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)35,36). Studies on additional pharmacological properties of the teas and species are currently in progress.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations